Pengaruh Cash Ratio, Gross Profit Margin (GPM), Debt To Equity Ratio (DER), Dan Earning Per Share Terhadap Peringkat Obligasi - Risfa Aryani Putri; Nor Norisanti; Erry Sunarya (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study is to determine the effect of Cash Ratio, Gross Profit Margin (GPM), Debt To Equity Ratio (DER), Earning Per Share (EPS) on Bond Ratings in basic industrial and chemical sector companies listed on the Indonesia Stock Exchange for 2021-2022 for 32 quarters. The samples used were 32 out of 48 samples with purposive sampling techniques. The data analysis technique uses multiple linear regression analysis with data processing using SPSS 25 software. The results showed a variable relationship between Cash Ratio, Gross Profit Margin (GPM), Debt To Equity Ratio (DER), and Earning Per Share (EPS) to Bond Rating of 0.670 (strong). Cash Ratio positively affects the Bond Rating of 0.406 or 40.6%. Gross Profit Margin (GPM) negatively affects the Bond Rating by 0.100 or 10%. The Debt To Equity Ratio (DER) negatively affects the Bond Rating by 0.001 or 0.01%. Earnings Per Share (EPS) negatively affects a Bond Rating of 0.005 or 0.05%. Keywords: Cash Ratio, Gross Profit Margin (GPM), Debt To Equity Ratio (DER), Earning Per Share (EPS), Bond Rating.